Young Musicians' Learning of Expressive Performance: The Importance of Dialogic Teaching and Modeling - Meissner, Henrique; Timmers, Renee (Frontiers in Education, 2020)
Until recently little was known through systematic research about effective teaching methods to enhance children’s expressiveness in music performance. A previous experimental study indicated that a dialogic teaching approach, consisting of questions and dialogue, improves pupils’ expressive performance. Developing from this, a participatory action research study was conducted with the following objectives: 1) to explore how dialogic teaching and learning of expressiveness can be used in weekly individual instrumental lessons; 2) to investigate whether instrumental tutors find a dialogic teaching approach useful for facilitating pupils’ learning of expressiveness; and 3) to explore what other complementing instructional modes tutors would like to employ. 4) To investigate pupils’ views on their learning of expressiveness; and (5) pupils’ views on the instructional strategies used for teaching expressiveness. Five instrumental music tutors participated in this research with two or three of their pupils (11 girls in total, aged 8-15, playing various instruments) for four months. Pupils played in informal performance sessions at the start, middle and end of the project. Lessons and performances were video-recorded. Music diaries, questionnaires and video-stimulated recall interviews were used to collect information about participants’ views. Participating tutors used mainly dialogic teaching, modeling and playing along with pupils. Tutors thought that teaching and learning expressiveness is a complex process wherein “everything is intertwined”; several methods can be used within a dialogic teaching approach for working on various teaching aims. Aural modeling combined with dialogic teaching was seen as especially useful. Pupils’ accounts indicate that they had learned to think about the musical character and how to convey this in performance. Tutors’ questions had stimulated pupils’ reflection and raised their awareness of the musical meaning, while teachers’ modeling had helped to build up an aural picture of the music which had facilitated pupils’ learning. The dialogic teaching approach supported by modeling had generated improved expressiveness in lessons and contributed to a growing sense of achievement, confidence, self-efficacy and musical agency. These findings demonstrate the importance of dialogic teaching supported by modeling for meaningful instrumental music education as this can stimulate pupils’ thinking, thus facilitating their learning and enhancing their expressiveness.